Memorandum of Understanding between the Human resource development of Korea and BRAC University (2011) - Human Resources Development of Korea; BRAC University (Human resources development of Korea and BRAC University, 2013)
Memorandum of Understanding between human resource development of Korea ("HRDK", which expression shall include its successors-in-title, licensees and assigns) AND BRAC University ("BRAC", which expression shall include its successors-in-title, licensees and assigns).